Serum CETP status is independently associated with reduction rates in LDL-C in pitavastatin-treated diabetic patients and possible involvement of LXR in its association. Issue 1 (December 2016) - Shimada, Akihiro; Kimura, Hideki; Oida, Koji; Kanehara, Hideo; Bando, Yukihiro; Sakamoto, Shinobu; Wakasugi, Takanobu; Saga, Takashi; Ito, Yasuki; Kamiyama, Kazuko; Mikami, Daisuke; Iwano, Masayuki; et al.
Abstract Background Statins decrease cholesteryl ester transfer protein (CETP) levels, which have been positively associated with hepatic lipid content as well as serum low density lipoproteins-cholesterol (LDL-C) levels. However, the relationship between the CETP status and statin-induced reductions in LDL-C levels has not yet been elucidated in detail. We herein examined the influence of the CETP status on the lipid-reducing effects of pitavastatin in hypercholesterolemic patients with type 2 diabetes mellitus as well as the molecular mechanism underlying pitavastatin-induced modifications in CETP levels. Methods Fifty-three patients were treated with 2 mg of pitavastatin for 3 months. Serum levels of LDL-C, small dense (sd) LDL-C, and CETP were measured before and after the pitavastatin treatment. The effects of pitavastatin, T0901317, a specific agonist for liver X receptor (LXR) that reflects hepatic cholesterol contents, and LXR silencing on CETP mRNA expression in HepG2 cells were also examined by a real-time PCR assay. Results The pitavastatin treatment decreased LDL-C, sdLDL-C, and CETP levels by 39, 42, and 23 %, respectively. Despite the absence of a significant association between CETP and LDL-C levels at baseline, baseline CETP levels and its percentage change were an independent positive determinant for the changes observed in LDL-C and sdLDL-C levels. The LXR activation with T0901317 (0.5 μM), an in vitro condition analogous to hepatic cholesterol accumulation, increased CETP mRNA levels in HepG2 cells by approximately 220 %, while LXR silencing markedly diminished the increased expression of CETP. Pitavastatin (5 μM) decreased basal CETP mRNA levels by 21 %, and this was completely reversed by T0901317. Conclusion Baseline CETP levels may predict the lipid-reducing effects of pitavastatin. Pitavastatin-induced CETP reductions may be partially attributed to decreased LXR activity, predictable by the ensuing decline in hepatic cholesterol synthesis. Trial registration UMIN Clinical Trials Registry IDUMIN000019020